Complementary food hygiene practice and associated factors among mothers with children aged 6–23 months in Dessie Zuria, South Wollo Zone, Amhara, Ethiopia, 2023 - Addis, Alemayehu Tesfaye; Dawed, Yeshimebet Ali; Yimer, Geleta Mussa; Adem, Yonas Fissha (Frontiers in Nutrition, 2024)
Background: It's critical to implement appropriate complementary food hygiene practices to lower the incidence of foodborne disease and malnutrition in children. It is overlooked in resource-limited settings and information regarding this practice is not fully available and assessed enough. Therefore, this study aimed to assess complementary food hygiene practices and their associated factors in Dessie Zuria, South Wollo Zone, Amhara, Ethiopia, 2023. Methods: An institutional-based cross-sectional study design was conducted from April 17 to May 18, 2023, among 366 mothers who had children aged 6–23 months. Dessie Zuria was purposively selected, and a systematic random sampling technique was used to get the study participants. Data was collected using pretested and structured questionnaires. Finally, data was entered using EPI-info and then exported to SPSS version 26. Bi-variable and multi-variable logistic regressions were used to identify factors associated with complementary feeding hygiene practices. Both crude odds ratios (COR) and adjusted odds ratios (AOR) with a 95% confidence level (CI) were computed, and a P-value <0.05, in the final model, was considered statistically significant. Result: The proportion of complementary food hygiene practices was 22.22 % and household access to media like TV or radio (AOR=10.51, 95% CI: 2.8, 39.28), starting complementary feeding before 6 months (AOR=2.01,95%CI:1.05, 3.84) and child's age 6 to 11 months old (AOR=0.25, 95% CI:0.08, 0.7) were found associated factors of complementary food hygiene practices. Conclusion: the prevalence of complementary food hygiene practices was poor. Healthcare professionals should promote starting breastfeeding at the age of 6 months. Additionally, media companies ought to make an effort to create a positive social and cultural environment that encourages complementary feeding practices for young children.